2017
DOI: 10.1017/s003329171700068x
|View full text |Cite
|
Sign up to set email alerts
|

Backing into the future: pharmacological approaches to the management of resistant depression

Abstract: Pragmatic studies indicate that a substantial number of depressed patients do not remit with current first-line antidepressant treatments and after two failed treatment steps the chance of remission with subsequent therapies is around 15%. This paper focuses on current evidence for pharmacological treatments in resistant depression as well as possible future developments. For patients who have failed to respond to two antidepressant trials, augmentation with atypical antipsychotic drugs, specifically quetiapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
2
26
0
1
Order By: Relevance
“…Indeed, in observational studies pramipexole was prescribed at flexible and higher doses than in RCTs . These results are supported by other authors , who underscored the importance of adequate dosage for pramipexole to exert its full effect. Observational studies reported higher response and remission rates than RCTs also for traditional antidepressants .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Indeed, in observational studies pramipexole was prescribed at flexible and higher doses than in RCTs . These results are supported by other authors , who underscored the importance of adequate dosage for pramipexole to exert its full effect. Observational studies reported higher response and remission rates than RCTs also for traditional antidepressants .…”
Section: Discussionsupporting
confidence: 54%
“…In the last 15 years, substantial efforts have been made to evaluate the efficacy and the safety of pramipexole for the treatment unipolar and bipolar depression, both in monotherapy and as adjunctive treatment. The available reviews focused on a limited number of trials , or on randomized controlled trials (RCTs) , or on trials including only patients with bipolar depression .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that the physical state affects emotional health . Several hypotheses concerning the mechanisms whereby inflammation potentially influences emotional health have been put forward, including dysregulation of the hypothalamic pituitary adrenal axis, changes in glial function and glutamate release in the brain, and activation of the tryptophan metabolizing enzyme . Of particular interest are findings of clinical studies showing that antiinflammatory drugs are effective in treating patients with depression .…”
Section: Introductionmentioning
confidence: 99%
“…to the United States Food and Drug Administration (FDA) received approval for use in addition to antidepressants in the treatment of a severe depressive episode. [11][12][13][14] In this case, it was shown that the combination of antidepressants with aripiprazole led to the withdrawal of the symptoms of depression, with long-term persistence and without the occurrence of subsequent sudden mood disorders. Bearing in mind the long history of use of antidepressants and psychotherapy combined, which gave no desired results, it was concluded that adding of aripiprazole as an additional therapy proved to be extremely useful.…”
Section: Discussionmentioning
confidence: 99%